The Role Of The Community In Increasing Sharia Financial Literature And Inclussion - Mujiatun, Siti (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2023)
People are still not aware of the surrounding digital environment so they cannot use their income to save, invest, protect and meet economic needs. The purpose of this study is to determine the role of the community in improving financial literacy and financial inclusion, using library research methods in the form of books, journals, and issues that are currently developing. The result of the research is that with the advantages that the sharia community has as an inseparable part of the social system of the Muslim community in Indonesia, the community has the potential to play its role in developing Islamic financial literacy and inclusion in Indonesia. The potential possessed by the community at least includes, among others, helping to support the National Strategy for Indonesian Financial Literacy; mediator development of Islamic financial literacy and inclusion through social capital; and open cooperation with a participatory culture.  Keywords: Community, Financial Literature, and Financial Inclusion